The Effectiveness of Career Guidance Services in Increasing the Interests of Students Who Can't Able To Continue Their Studies - Kusmiatun (Penerbit Hellow Pustaka, 2023)
This paper was created to find out the implementation and effectiveness of career guidance services at SMA Negeri 1 Loh Bener so that we can clearly see how the role of counseling teachers plays in the careers of class XII students, especially students who can't afford it. The type of this research is field research using descriptive research methods with a qualitative approach. The research technique used is data collection techniques and data analysis techniques. Data collection techniques were carried out by means of observation, interviews and documentation. The results of this study are 1. The career guidance service at SMA Negeri 1 Lohben consists of 5 stages as follows: a). Counseling teachers collect student data to find out whether or not students are interested in continuing their studies. B). Implementation of career counseling in which students will get questions about whether or not they are interested in continuing their studies, c). Counseling guidance teachers provide information via information boards containing lecture and job brochures, d). Counseling guidance teachers have the opportunity to enter classes to provide career information, e). Guidance and counseling teachers help students who are unable to continue their studies. 2. The effectiveness of career guidance services in increasing the interest of students who are unable to continue their studies has fulfilled the needs that students want, namely the existence of information boards, socialization of State Universities (PTN), guidance and counseling teachers who always provide services both individual and group counseling regarding careers , make students happy and get very extensive career information.